Pengaruh Penambahan Limbah Flue Gas Desulfurization Gypsum Terhadap Karakteristik Tanah Lempung - Apriyanti, Yayuk; Lestari, Nova Dinda; Fahriani, Ferra; Hisyam, Endang S; Anugra Sandy, Boy Dian (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Clay soil is a type of soil that has problems because it has high plasticity, a low carrying capacity, and is prone to settlement. This soil condition can be found in the Hanging Tramble, Pangkalpinang City. This study aims to determine the effect of FGD waste gypsum on clay soils, the maximum value of soil shear strength, and the minimum value of soil consolidation settlement. The stabilizing agent used in this study was Flue Gas Desulfurization ( FGD) waste gypsum with a mixture of 10%, 15%, and 20% FGD waste gypsum from the dry weight of the soil., for a total of 39 samples of the test object. Testing in this research uses Indonesian National Standards (SNI).The test results obtained the maximum value of the shear strength of the soil in the FGD waste variations of gypsum at 15%, which is 115.243 kN/m2, and in the 20% FGD gypsum waste mixture, the value of the shear strength of the soil decreased by 79.634 kN/m2. The minimum value for consolidation settlement was obtained from FGD waste variations (gypsum 20%), which is 0.683 cm. The minimum value obtained for consolidation settlement is influenced by the calcium content in the FGD waste gypsum, which can bind soil minerals so as to increase soil strength. It can be concluded that the maximum soil shear strength value occurs in the 15% FGD waste mixed sample variation gypsum, while the minimum soil consolidation settlement value is in the 20% mixed FGD waste mixture gypsum.